The Development of Indonesian Vocabulary in the Digital Era: A Literature Review on Neologisms and Linguistic Adaptation in Information Technology - , Elistyani; I Made Juliarta; Komang Astiari (Universitas Bali Dwipa, 2025)
This literature review examines the development of Indonesian vocabulary in the digital era, focusing on neologisms and linguistic adaptation within information technology contexts. The study employs a qualitative literature review methodology, analyzing scholarly publications from 2020 to 2025 to understand patterns of vocabulary development, sociolinguistic factors, and integration processes in contemporary Indonesian usage. The analysis reveals five distinctneologism formation patterns: direct borrowing from English, hybrid formation combining foreign elements with Indonesian morphological structures, extensive use of acronyms and abbreviations, morphological creativity through affixation processes, and semantic extension of existing Indonesian words to accommodate digital meanings. Sociolinguistic factors significantly influencing vocabulary adaptation include generational differences, educationalbackground, urban-rural divides, social media platform preferences, professional domain requirements, and regional linguistic variations. Integration levels vary considerably across different contexts, with terms like